Ганжурыг орчуулахад Аюуш гүүшийн оролцсон тухай - Д.Бүрнээ (Acta Mongolica, 2007)
Mongolian sources of the middle ages such as "Chakravardi Altan khaanii tuuj" and "Erdeniin tovch" noted that Ayush guush was awarded with the title "Ananda Manzushiri Guush" by the Third Dalai Lama for his translation merit. Therefore, in the Colophon of Mongolian handwritten and printed Kanjur, we can see his name only under this title. As noted Mongolian sources in Colophon of Mongolian Kanjur, he played a main role in the translation work of Kanjur together with the famous translator, Shireet guush. We found his name nine times in the Colophon of Mongolian handwritten Kanjur and ten times in the Colophon of Mongolian printed Kanjur. In total, he translated 11 works, out of which he translated 5 works by himself and 6 works with others. We think that the name, Choiji-Odser mentioned in the Colophon of Kanjur as a supervisor of Ayush Guush, is the famous translator Samdansengge.